2021
DOI: 10.1002/aoc.6442
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a sustainable heterogeneous catalyst, titanium dioxide‐loaded hydroxyapatite for functionalised chromen‐dihydropyridines under green conditions

Abstract: We have described the synthesis of composite materials with different titanium dioxide loading on hydroxyapatite (TiO2/HAp). Their structural properties and morphologies were established by powder X‐ray diffraction (p‐XRD), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET), transmission electron microscopy (TEM) and Fourier transform infrared (FT‐IR) analyses. The catalytic efficacy of the as‐prepared composite materials was explored to synthesise novel 4‐oxo‐chromen‐dihydropyridine derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The peaks at 1632 and 3431 cm –1 were attributed to the absorption of water molecules present in the atmosphere by the nanoparticles during analysis. The presence of hydroxyl groups in the synthesized Ti–O was confirmed by bands appearing at 2359 and 3424 cm –1 , and the peak value was 616 cm –1 due to the widening and overlapping of HAp phosphate groups, which indicated that TiO 2 –HAp composite nanomaterials were formed due to the addition of Ti–O. Furthermore, as illustrated in Figure c, a discernible transition is observed from the bottom to the top, where the primary crystal plane gradually shifts from a lower to a higher orientation, while the main diffraction peak region transitions from narrow to wide. Notably, TiO 2 @PF-127@CBM and TiO 2 –HAp@PF-127@CBM exhibit an additional minor crystal plane, although smaller in size.…”
Section: Results and Discussionmentioning
confidence: 86%
“…The peaks at 1632 and 3431 cm –1 were attributed to the absorption of water molecules present in the atmosphere by the nanoparticles during analysis. The presence of hydroxyl groups in the synthesized Ti–O was confirmed by bands appearing at 2359 and 3424 cm –1 , and the peak value was 616 cm –1 due to the widening and overlapping of HAp phosphate groups, which indicated that TiO 2 –HAp composite nanomaterials were formed due to the addition of Ti–O. Furthermore, as illustrated in Figure c, a discernible transition is observed from the bottom to the top, where the primary crystal plane gradually shifts from a lower to a higher orientation, while the main diffraction peak region transitions from narrow to wide. Notably, TiO 2 @PF-127@CBM and TiO 2 –HAp@PF-127@CBM exhibit an additional minor crystal plane, although smaller in size.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Recently, our research group has focused on exploring a range of environmentally friendly protocols to produce novel heterocycles with a range of biological activities, like antimicrobial, antioxidant, anticancer, and anti‐diabetic agents 55–58 . These methods include heterogeneous catalysis, microwave irradiation, and ultra‐sonication 59–63 . In our quest for the most efficient synthetic technique, we present a successful way to produce hexahydroquinolines employing a multi‐component single‐step reaction consisting of substituted aldehydes, ethyl aceto‐acetate, NH 4 OAc, and cyclohexadione.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58] These methods include heterogeneous catalysis, microwave irradiation, and ultra-sonication. [59][60][61][62][63] In our quest for the most efficient synthetic technique, we present a successful way to produce hexahydroquinolines employing a multi-component single-step reaction consisting of substituted aldehydes, ethyl aceto-acetate, NH 4 OAc, and cyclohexadione. This synthesis is carried out in the presence of a novel nanocomposite catalyst under mild reaction conditions using an EtOH solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The prominence of viable heterogeneous catalysts and economic advantages is being revived through efficient green protocols, which are considered vital in improved organic synthesis [ 21 , 22 , 23 ]. In particular, one-pot synthetic methodology protocols under green conditions of heterocyclic analogues have become a sizable alternative in modern organic chemistry to conventional multistep synthesis [ 24 , 25 , 26 , 27 ]. Because of the improved productivity and substantial time saving, multicomponent reactions (MCRs) are recognised as reliable synthetic green methodologies [ 21 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%